The Knowledge Level of Primary Care Physicians in Surabaya Primary Health Care Center Concering Hepatitis B - Ummi Maimunah; Rudyanto Rudyanto; Poernomo Boedi Setiawan; Pangestu Adi; Iswan Abbas Nusi; Hernomo Ontoseno Kusumobroto (The Indonesian Society for Digestive Endoscopy, 2010)
Background: One of physician’s functions at primary health care center (PHC) is the ability to diagnose some diseases especially that contribute to high morbidity and mortality. Until now, hepatitis B virus infection has become a major health problem worldwide. The aim of this study was to identify the knowledge level of primary care physicians concerning hepatitis B in Surabaya. Method: The present study was a cross-sectional study that performed by investigators through interviews with primary care physicians in Surabaya to fill questionnaires for measuring their knowledge level. The questionnaires were modified from questionnaire survey in Tur Key performed by Peksen et al. It reflected the level of knowledge of the physicians including their comprehension, application and analysis. Validity and reliability test were performed on the Result of those questionnaires. The knowledge level was categorized as follows: 75 (excellent), 70.0–74.9 (very high), 65.0–69.9 (high), 60.0–64.9 (medium), 55.0–59.9 (moderate), 47.5–54.9 (nearly moderate), 40.0-47.4 (less moderate), 40 (low). Results: Based on validity test, we obtained 14 items of 17 question items with correlation coefficient 0.287–0.561 and alpha reliability index 0.639; therefore, the instrument can be used to measure the knowledge level. The results of mean score conversion included comprehension, which was 84.878 ± 16.499 (excellent category); application, which was 47.556 ± 31.870 (nearly moderate category) and analysis, which was 14.634 ± 35.562 (low category). Statistically, the mean value of the knowledge level scale, which was the combination of comprehension, application and analysis, was obtained at 49.023 ± 19.085 including the nearly moderate category. Conclusion: By using a valid and reliable instrument, the knowledge level of primary care physician in Surabaya concerning hepatitis B can be categorized as nearly moderate. Keywords: hepatitis B, liver cirrhosis, hepatoma